(untitled) (ACME, 2017)
This paper addresses eighteenth-century women’s travel writing outside Europe from the perspective of their representation of the (foreign) body. The assumption is that while gazing at the others’ bodies, women were forcing themselves into a perception of their own bodies as clearly distinct from or as cognate to the foreign ones. The examples provided aim at showing how the representation of other bodies calls for an acknowledgment of domestic cultural issues, whether the debate is on ethical problems like slavery or over the social status of women, or simply over codified cultural symbols. Behn, Justice, Montagu, Vigor, Kindersley, Schaw, Craven, Falconbridge, Parker, Fay constitute the corpus of authors considered, all of them recording travels to far away unusual destinations.